Strategi Active Learning Model Index Card Match dalam Upaya Meningkatkan Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Kelas XI di Madrasah Aliyah Negeri 3 kebumen - Saiful Amin; Bahrun Ali Murtopo (IAINU Kebumen, 2026)
This study aims to describe the application of the Active Learning strategy of the Index Card Match model in improving the learning outcomes of students of Islamic Religious Education (PAI) class XI at MAN 3 Kebumen. Using descriptive qualitative methods with observation, interview, and documentation techniques, the results showed that the application of this strategy through the preparation, implementation, and evaluation stages was able to increase the average student score from 68.5 to 80.2, with classical completeness increasing from 40% to 78% and learning activity reaching 85%. In addition to cognitive improvement, this strategy also encourages the development of affective and psychomotor aspects such as motivation, cooperation, and responsibility. Thus, the Index Card Match model has proven to be effective in creating active, interactive, and fun PAI learning and improving student learning outcomes.